Daya Terima Fortifikasi Tepung Eucheuma Cottonii pada Produk Dimsum sebagai Alternatif Pangan Kaya Serat - Nathasa Weisdania Sihite; Eliza Eliza; Elva Amurita Zebua (Poltekkes Kemenkes Padang, 2023)
Fortification, which is known as food enrichment for processed food products, has recently been frequently studied. The fortification of Eucheuma cottonii seaweed flour was carried out to manufacture dimsum products that aim to produce fiber-rich food. This research aims to analyze the acceptability of Eucheuma cottonii flour fortification on dimsum, and to analyze the proximate content of the product by chemical analysis. The method used in this study is experimental research, with a completely randomized design (CRD) with three formulas, namely F1 (25%), F2 (45%), and F3 (55%). Data had analyzed statistically with the non-parametric Kruskal Wallis-Mann Whitney test. Based on the test results, it was explained that there was a significant effect of color (p=0.047), taste (p=0.004), and texture (p=0.000). The results explained that the fortification of Eucheuma cottonii flour affected the color, taste, and texture and the color of the dimsum became grainy (sticky, grainy, and chewy). The addition of fortified seaweed flour (Eucheuma cottonii) can increase the percentage of fiber in dimsum products, namely dietary fiber (3.24-3.80% body weight) and crude fiber (0.37-0.49% body weight). The research concluded that fortification of Eucheuma cottonii flour was organoleptically acceptable and could use as a menu recommendation for food products that are high in fiber. It is necessary to pay more attention to the determination of the flour concentration level in detail because the main component of seaweed is colloidal.